2011
DOI: 10.1159/000325662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subcortical Vascular Ischemic Dementia and Aging on Negative and Neutral Word List Learning

Abstract: Background: Subcortical ischemic vascular dementia (SIVD) represents an important subgroup of vascular dementia. Besides characteristic cognitive deficits, particular emotional problems support the diagnosis. Emotional disturbances in SIVD are not well understood. Method: We studied the performance of SIVD patients, healthy young control persons and old control persons in an emotional word list learning task. Results: SIVD patients showed lower memory performance than both control groups for neutral as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…garbage, fire, poison, gun) words. In 2011, Billino et al reported results of their study about the performance on an emotional word list learning task of fourteen patients with subcortical ischemic vascular dementia (SIVD), a diagnosis supported by emotional incontinence and lability [17]. Patients' performance was compared with that of healthy young control persons (n=14) and old control persons (n=14).…”
Section: Wordsmentioning
confidence: 99%
“…garbage, fire, poison, gun) words. In 2011, Billino et al reported results of their study about the performance on an emotional word list learning task of fourteen patients with subcortical ischemic vascular dementia (SIVD), a diagnosis supported by emotional incontinence and lability [17]. Patients' performance was compared with that of healthy young control persons (n=14) and old control persons (n=14).…”
Section: Wordsmentioning
confidence: 99%